Treatment of Advanced Prostate Cancer: Where Are We in 2019? - Monteiro, Fernando Sabino Marques; Soares, Andrey; Oliveira, Fernando Nunes Galvão de; Crivelaro, Pedro Castilhos de Freitas; Barrios, Pablo Moura; Fay, Andre Poisl (Brazilian Journal of Oncology, 2019)
In the last decade, important advances have been made in the treatment of metastatic prostate cancer, resulting in a better understanding of the biology underlying the disease, and in the approval of several therapeutic agents such as immunotherapy, new generation antiandrogens, cytotoxic chemotherapies, and radiopharmaceuticals. All these recent advances have been incorporated in clinical guidelines and a critical analysis of the data available should be important to help the decision-making process. In addition, the incorporation of well established therapies in early disease stages have demonstrated a robust overall survival gain for patients with castration-sensitive metastatic prostate cancer. However, no predictive biomarkers of response are available and the selection of the best therapeutic option is still challenging depending on clinical and pathological factors. Many questions related to the optimal sequencing of agents, or comparison of its efficacy remain unanswered.
Keywords: Prostate; Review/drug therapy; Receptors; Androgen; Androgen Antagonists; Advanced Treatment; Prostate-Specific Antigen